Fabric selection for speed skating suits based on the atmospheric conditions and the athletes morphology - Suzuki, K.; Yamanobe, K.; Maeda, A. (Journal of High Performance Sport, 2023)
Aerodynamic drag in speed skating is also reduced by equipment. Among them, many studies have been reported on the reduction of aerodynamic drag by suits. However, the relationship between the aerodynamic properties of grooved knit fabrics and the change in their micro-surface shape has not been clarified. Therefore, this study conducted the circular cylinder model wind tunnel experiments on two types of grooved knit fabrics (Type A and Aerodynamic drag in speed skating is also reduced by equipment. Among them, many studies have been reported on the reduction of aerodynamic drag by suits. However, the relationship between the aerodynamic properties of grooved knit fabrics and the change in their micro-surface shape has not been clarified. Therefore, this study conducted the circular cylinder model wind tunnel experiments on two types of grooved knit fabrics (Type A and Type B) with different micro-surface shapes. In addition, a full-scale model of a skater wind tunnel experiments were conducted on two types of one-piece suits (Suit A and Suit B) with different grooved knit fabrics used near the thighs. In the circular cylinder model experiment, the onset of criticality for Type A was in the lower speed range than for Type B. In a full-scale model of a skater experiment, the onset of criticality was slower in Suit A than in Suit B. Groove depth (Type A>Type B) may have affected the criticality. In addition, it is necessary to consider the environment of the competition venue, the physique of the athlete, and the speed of the skater when choosing between grooved knit fabrics. Suit A and Suit B use for 0.45 m (height 1.58 m) <=L>=0.53 m (height 1.84 m) at Heerenveen (elevation 0 m) was as follows. The Male 500 m was Suit B at any L, the Male 1000 m to 1500 m and Female 500 m to 1000 m events required the use of Suit A and Suit B depending on L, and the Male 5000 m and above and Female 1500 m and above were Suit A at any L.